Study of Student Behavior on the Implementation of Child Friendly School at SMA Negeri 8 Surakarta - Rui Arda, Extana; Septina Galih Pudyastuti; Danang Purwanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Juvenile delinquency is a problem that often occurs within the scope of educational units. Children also often get bullying treatment that can damage their mentality. The government provides a solution to this problem by creating a Child Friendly School policy. This program, which is located in formal, non-formal and informal education units, aims to create conditions that are safe, healthy, clean and can guarantee and fulfill children's rights. There is a guarantee in protecting children from violence, discrimination or treatment that endangers children and participating in providing the best service. Child Friendly Schools are a means for students to learn, develop and increase their learning motivation and self-confidence. The purpose of this study is to describe the form of Student Behavior Study of Child Friendly School Implementation at SMA Negeri 8 Surakarta. This type of research is descriptive with a qualitative approach. The focus of this research is on the objectives of the Child Friendly School program, the policies implemented and the reality of its implementation. Data collection techniques of this research through observation, interviews and documentation. Data analysis techniques in this study are data reduction, data presentation and conclusion drawing. Translated with DeepL.com (free version)The results obtained state that the implementation of the Child Friendly School program at SMA Negeri 8 Surakarta has been running but cannot be said to be optimal because in its realization there are still several violations that cannot be eliminated. There needs to be a review of this government program to produce the success of Child Friendly Schools. So that the program that has been pursued by the government can run optimally.